Migrating Words, Migrating Merchants, Migrating Law Trading Routes and the Development of Commercial Law - Gialdroni, Stefania; Cordes, Albrecht; Dauchy, Serge; De ruysscher, Dave; Pihlajamäki, Heikki (Legal History Library, 2019)
Migrating Words, Migrating Merchants, Migrating Law, edited by S. Gialdroni, A. Cordes, S. Dauchy, D. De ruysscher and H. Pihlajamäki, offers a transdisciplinary account of the connections between merchants' journeys, the languages they used and the development of commercial law. ; Readership: Scholars interested in commercial law history, economic history, history of linguistics, translation and, more generally, in the lives and travels of merchants and the impact they had on the development of law.